Comparison of the Microbiota and Inorganic Anion Content in the Saliva of Patients with Gastroesophageal Reflux Disease and Gastroesophageal Reflux Disease-Free Individuals - Ziganshin, Ayrat M.; Gogoleva, Natalia E.; Kiassov, Andrey P.; Saleeva, Gulshat T.; Akhmetova, Ramilya F.; Sagitov, Ildar I.; Ziganshina, Elvira E.; Shagimardanova, Elena I. (BioMed research international, 2020)
The oral cavity is one of the most complex microbial environments; however, the complex nature of the salivary microbiota and the level of inorganic anions in the saliva of subjects with and without gastroesophageal reflux disease (GERD) are poorly understood. The primary goals of this pilot research were to assess differences in salivary bacterial community composition and inorganic anion concentrations between patients with GERD and GERD-free people. Thus, the salivary microbiota within both groups was dominated by these genera: Streptococcus, Prevotella, Porphyromonas, Veillonella, Neisseria, Haemophilus, Fusobacterium, Rothia, and Leptotrichia. However, the relative abundances of the genera Actinomyces, Atopobium, Stomatobaculum, Ruminococcaceae_[G-2], Veillonella, and Leptotrichia were significantly higher in the saliva samples of patients with GERD, while the genera Porphyromonas, Gemella, Peptostreptococcus, and Neisseria were less abundant in this group. The concentrations of chloride, phosphate, and sulphate ions in the human saliva varied among all subjects and sampling time. These results broaden our knowledge of the salivary microbial community composition and chemistry of saliva of patients with GERD and GERD-free individuals.